On the behaviour of continuous RC slab strips flexurally strengthened by the NSM technique - Dalfré, Gláucia (2013)
This work explores the influence of the amount of CFRP in terms of load carrying capacity, ductility and moment redistribution capacity of continuous RC slab strips. In this way, for assessing the predictive performance of a FEM-based computer program, the experimental results obtained by Bonaldo (2008) and Dalfré (2013) were compared with values predicted by this software. Finally, a parametric study is carried out to investigate the influence of the strengthening arrangement and CFRP percentage in terms of load carrying capacity and moment redistribution capacity of continuous RC slab strips flexurally strengthened by the NSM technique.